A Remote Lab for Industrial Electronics Course - A. S. Araújo (2009)
The presented Remote Lab is currently available in the Industrial Electronics course, at Faculty of Engineering of PortoUniversity (FEUP), it is a result of the Labs-on-the-Web POCI 2010 Project, and intends to put available, remotely, some ofthe experiments usually done in traditional labs, as well as presented in lecture classes, in the Industrial Electronics Course atFEUP.In order to do so, we used the MOODLE e-learning system, National Instruments NI ELVIS and Lab View in a Remote Labplatform that has a set of linked computers in a local net. Connection to external users, by Internet, uses a Firewall. One of thecomputers is the Moodle and videoconference Flash Communication Server. Each remote experiment has its own, virtualinstrumentation, Lab VIEW web server, and webcam. On-line access to remote lab experiences is carried out through Moodleenvironment.